278 Impact of specific prevention training measured by the star excursion balance test modified (SEBTm) in young female soccer: a cluster randomised controlled trial. (3rd March 2020) - Rabal, Hugo Del; Picot, Brice; Rambaud, Alexandre
Abstract : Background: Use of SEBTm can identify athletes with risk of injury and help to set up prevention strategies. Objective: To identify subjects at risk of lower limb injuries (LLI) with SEBTm after a specific prevention training. Design: Cluster randomised controlled trial. Setting: French elite soccer youth academy. Patients (or Participants): 36 healthy female athletes (aged 15–19 years old) were included and assigned to the 'Control Groupe' (CrtGrp) or 'Prevention Training Group' (PrevGrp) by a cluster randomised controlled trial. Interventions (or assessment of risk factors): Both groups performed normal 5 weeks pre-season training, but in the 'intervention' we implemented a specific prevention protocol based on international recommendations. Main outcome measurements: Composite score (CS) of SEBTm were measured in both group at baseline (T0), after 5 weeks (post–protocol) and 3 months after the end of the protocol. Furthermore a 10 month follow up questionnaire post protocol was used to asses LLI in the two groups. Results: After 5 weeks and exclusion criteria, 28 players completed the all study (16 in the control group and 12 in the intervention group). After the protocol period, CS increased significantly in the PrevGrp (p=0, 03). In the CrtGrp, no difference was seen between the 2 testing sessions (p=0, 68). Based on injury risk factors, 19 subjects were identified as 'at risk' at T0. Of these, 4 players had at-least 1 LLI after 10 months (RR=0, 67). Moreover, 2 subjects who were not identified 'at risk' sustained a LLI during during the 10 months period. After 5 weeks, 2 of the 12 subjects in the PrevGrp exceeded the SC cut-off, compare to 0 on 16 players in the CrtGrp. Conclusions: This study suggests that the prevention training program seems to improve the SC at SEBT. This could leed to a diminished risk to sustain an LLI. These results needed to be confirmed with larger sample size studies.